A Novel Clinical Scoring Model for Interventional Therapy in Chronic Total Occlusion of the Coronary Artery - Bin Xiao; Lang Hong; Xinyong Cai; Hongmin Zhu; Bin Li; Liang Shao (Journal of Interventional Cardiology, 2021)
Objective. With the rapid development of technology and experience, the current percutaneous coronary intervention of chronic total occlusion (CTO-PCI) preoperative scoring model needs to be updated. This study aimed to evaluate the clinical value of the operator-CTO score in predicting the outcome of interventional therapy for chronic total occlusion of the coronary artery. Methods. The data of 144 lesions in 130 patients with CTO were analyzed prospectively. The CTO procedures were performed by 10 operators with different skills and experiences. Before the procedures, J-CTO, progress, ORA, recharge, and operator-CTO scores were determined. Then, the clinical, imaging, and procedural data of patients in different operator-CTO score groups and between different operators were compared. The final focus was on comparing the predictive ability of each score on the outcome of CTO-PCI. Results. The overall technical and procedural success rates were 90.9% and 88.9%, respectively. A decreasing trend in the technical success of CTO-PCI was observed according to the operator-CTO score hierarchy of “easy (≤2 points), moderate (3 points), difficult (4 points), and extremely difficult (≥5 points)” (99.0%, 87.5%, 53.8%, and 25.0%, respectively). All five scoring models were well calibrated, and the area under the curve (AUC) for the operator-CTO score was 0.901 (95% CI: 0.821–0.982, P<0.01), larger than the AUC for the remaining four scoring models, showing excellent ability to predict technical outcomes. Conclusion. The operator-CTO score is a new clinical scoring tool that can predict the outcome of CTO-PCI and can be used to grade the difficulty of the procedure, with the potential to work well with a broad group of operators.